SCENARIOS OF THE DEVELOPMENT OF ENTERPRISES OF THE TOURIST INDUSTRY OF UKRAINE IN THE CONDITIONS OF THE WAR AND POST-WAR PERIODS - Lubov Kvasnii; Olena Moravska; Lyubov Malyk; Yurii Shulzhyk; Olena Orlova; Oresta Scherban (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The purpose of the article is to study the factors of the development of enterprises in the tourism industry of Ukraine and the formation of scenarios for their development in the conditions of martial law and after the end of hostilities. When conducting the research, the methods generally accepted in economic science were used: monographic, dialectical - in the process of researching the development of enterprises of the tourism industry of Ukraine under martial law and after the end of hostilities; analysis and synthesis, grouping - to determine the factors of development of tourism industry enterprises; generalization and analysis, economic-statistical, abstract-logical and system-structural - for the formation of scenarios for the development of enterprises of the tourism industry of Ukraine. The key problem of the study is russia's attack on Ukraine, which turned into a heavy blow to the country's tourism. The article proves that protectionism and international conflicts threaten freedom and freedom to travel. All these changes mean that we are going through a period of great destabilization. It is justified that the reality as we know it, with a Europe without border crossings, may soon disappear. Emphasis is placed on the fact that it is important to create such tourist programs now so that not only Ukrainians but also tourists from other countries understand what was happening in Ukraine and tell about the struggle of Ukraine. Four scenarios for tourism development in Ukraine have been proposed, each with a number of implications for stakeholders. Based on the conducted scientific research, it was concluded that one of the optimal approaches to the formation of scenarios for the development of tourism industry enterprises in Ukraine in the conditions of universal dynamism, unpredictability and variability of the business environment is recognized as strategic management and change management. The practical significance of the obtained results reveals the prospects for applying the main scientific provisions of the article in the practice of managing tourism business enterprises in Ukraine in the conditions of post-war reconstruction. The results of the study presented in the work can be used by economists, scientists and practitioners to implement scenarios for the development of tourism industry enterprises in Ukraine, each of which has a number of consequences for stakeholders.